Experience in Teaching Mendeleev’s Periodic Law at National Research University - O. V. Mikhailov (Высшее образование в России, 2019)
The article discusses the questions concerning the presentation of the essence of the D.I. Mendeleev’s Periodic Law in the modern educational process in the framework of general educational and special chemical disciplines “General Chemistry”, “Inorganic Chemistry” and others. Some incorrectness have been noted both in the formulation of the Periodic Law itself and in the formulations of principles that are fundamental to the interpretation of this law (Hund’s rule, Pauli’s principle, Klechkovsky’s rule). Also, the article proposes the amended formulations of Mendeleev’s Periodic Law and each of these three principles.